The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae). Part IV: the C. eldae species group, with the description of three new species - Bordera, Santiago; Palacio, Edgard (Zootaxa, 2019)
The Neotropical Clistopyga eldae species-group is revised. Three species, C. catarina, C. marcapatensis and C. polita, are described as new. The species C. eldae Gauld, 1991 is redescribed, and an illustrated identification key to all species of the group is provided.